Ocena zrуїnicowania rodzajуw kolumn жwiczebnych stosowanych w grach i zabawach ruchowych - Winczewski, Piotr; Vynchevskyi, Petro (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У представленому дослідженні розглянуто різні варіанти організації учнів і керівництва ними в процесі проведення рухливих ігор. Проведено аналіз рекомендованих різними авторами варіантів організації 1869 ігор, які описані в навчальних посібниках для вчителів фізичного виховання. Дослідження показали, що частина авторів навчальних видань не приділяє уваги аспектам розподілу учнів за групами рівня, у яких вони повинні перебувати в процесі проведення гри, що ставить частину з них у нерівніумови, а внаслідок цього – до втрати інтересу до цієї їгри. Дослідження також показали, що запропонована форма організації рухливих ігор (особливо естафетного характеру) не повною мірою готує учнів до змагань. Відзначено також обмежену рухову активність учнів, а також недостатню їх підготовку щодо прояву ініціативи та взаємодопомоги установленні до своїх однолітків. In the presented study it was examined different variants of organization of pupils and their guidance in the process of conducting of outdoor games. It was conducted the analysis of recommended by different authors the variants of organization of 1869 games which are written in educational manuals for physical education. The studies have shown that some authors of educational manuals don’t pay attention to the aspects of dissemination of pupils into the groups equal according to their strength in which they should be placed in the process of game conducting that places some of them into unequal conditions and as a result leads to lost of interest to a particular game. The studies have also shown that presented forms of organization of outdoor games (especially of relay race character) don’t fully prepare pupils to outdoor games. Also it was indicated limited motor activity of pupils and insufficient their preparation in display of initiative and mutual help in relation to their peers.
Differentiated Estimation of the Variants of Organization of Pupils in the Process of Conducting of Outdoor Games
Keywords: Pedagogika zabawy; gry i zabawy ruchowe; kolumny жwiczebne; wychowanie fizyczne; games; construction; physical education